Structural Protective Design with Innovative Concrete Material and Retrofitting Technology - Wu, C.; Li, Jun (2017)
© 2017 The Authors. Retrofitting technology and high performance construction material are now widely investigated so as to increase structural ductility and robustness under extreme loading conditions. In the present study, some recent developments in structural protection against blast loads are compiled. Metallic foam materials with varying foam density and gradient are used in the cladding design, their energy absorbing capacities and stress-strain relationships are studied based on uniaxial compression tests. These foam material are used to cast sacrificial claddings on the concrete slabs in the field blast tests. Damage and structural deformation are measured to check the effectiveness of the claddings. Besides sacrificial foam cladding, concrete material with new reinforcement scheme including steel wire mesh and micro steel fiber is developed, and the static test results indicates the excellent ductility and crack control ability of this novel design. In the field blast tests, concrete slabs with different steel wire mesh reinforcement are exposed to varying blast loads. The effectiveness of the slab reinforcing design is discussed based on field performance.